Understanding the scientific contribution of an international community of researchers: the case of the IFIP WG 8.3 Conferences on DSS (1982–2014). (10th June 2016) - Csáki, Csaba; Meredith, Rob; O'Donnell, Peter; Adam, Frederic
Abstract: From its foundation in 1981, the goal of the International Federation of Information Processing (IFIP) Working Group 8.3 has been to share ideas about the design, development, use, and impact of systems intended to support decision makers and about the process of decision-making – in other words, to contribute to the accumulation of knowledge in the field of decision support systems (DSS). The working group organised its first conference in 1982 and up to 2014, the group has held twenty major conferences with published proceedings. These proceedings include over six hundred papers authored by researchers from over fifty countries. This paper presents the story of the group and the contribution of its members via a bibliometric analysis of the conference corpus. This analysis examines the themes and domains of the papers published by the working group over the decades. This includes statistics on the country, institutional and individual contributions as well as citations and referencing history. The paper concludes with a systematic review of the contribution of the international community of researchers who have become members of the working group over the years.